Longitudinal double-spin asymmetries for dijet production at intermediate pseudorapidity in polarized pp collisions at √s=200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review, 2018)
We present the first measurements of the longitudinal double-spin asymmetry ALL for dijets with at least one jet reconstructed within the pseudorapidity range 0.8<η<1.8. The dijets were measured in polarized pp collisions at a center-of-mass energy √s=200 GeV. Values for ALL are determined for several distinct event topologies, defined by the jet pseudorapidities, and span a range of parton momentum fraction x down to x∼0.01. The measured asymmetries are found to be consistent with the predictions of global analyses that incorporate the results of previous RHIC measurements. They will provide new constraints on Δg(x) in this poorly constrained region when included in future global analyses.
Gesehen am 05.07.2019